High intake of sweet foods and low life satisfaction can act as risk factors for acute coronary syndrome through synergistic interaction - So, Jisun; Chung, Kyong-Mee; Seo, Jihyeon; Kim, Byungmi; Chun, Hyejin; Han, Sung Nim; Chung, Ick-Mo (Frontiers in Nutrition, 2023)
Purpose Dietary and psychological status contributes to the development of coronary artery disease. However, these lifestyle factors may vary depending on ethnic and environmental background, and secondary prevention programs dealing with these factors in a specific population are not well-established. We aimed to assess dietary and psychological characteristics in Korean patients with acute coronary syndrome (ACS) and analyze their interactions as independent risk factors for ACS. Methods Ninety-two patients with ACS (29 acute myocardial infarction and 63 unstable angina) and 69 controls were subjected to dietary and psychological analyses. Dietary intake was assessed by a food frequency questionnaire. Psychological depression and perceived stress were assessed using the Patient Health Questionnaire-9 and the Perceived Stress Scale, respectively. Eight domains of life satisfaction (marital/love relationship, leisure, standard of living, job, health, family life, sex life, and self) were assessed using the Domain Satisfaction Questionnaire (DSQ). Results The ACS group had a higher consumption of sweets and fish/seafood, as well as higher levels of depressive symptoms. Additionally, they had lower DSQ scores in total, and all eight individual domains compared with the control group. In multivariate logistic regression analysis, sweet intake (OR 4.57, 95% CI: 1.94–11.40) and total DSQ scores (OR 0.34, 95% CI: 0.14–0.81) were identified as independent risk factors for ACS. Furthermore, these factors, which displayed a significant inverse correlation (ρ = −0.23, p = 0.01), were determined as having a synergistic contribution to the development of ACS. Conclusion High sweet food intake and low life satisfaction can act as risk factors for ACS through a synergistic interaction, which emphasizes a demand for a more comprehensive approach to secondary prevention of ACS. In addition, these data highlight the role of positive psychological wellbeing factors in cardiovascular health.